Achillea spp. - Edward F. Gilman; Terry DelValle (EDIS)
Achillea species are 18- to 36-inch-tall perennials that bear masses of flowers throughout the summer (Figure 1). The 60 to 100 species of yarrow are ancient, spreading, semi-evergreen herbs that are long lived. The aromatic, finely divided leaves are alternate or in basal rosettes. The leaf margins range from simple and toothed to pinnately dissected. However, most of these species have attractive feathery or fern-like foliage. The flowers may be single or double and come in shades of pink, yellow and white; flower heads are mostly in fine-textured corymbs. This document is Fact Sheet FPS-11, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 1999; reviewed October 2003.